CSR at Torrent Group - Barua, S. K. (Samir K.); Agarwalla, Sobhesh Kumar (London : Indian Institute of Management, Ahmedabad, 2020)
Corporate social responsibility (CSR) has emerged as an important area of corporate attention. In a world that is informationally integrated through the web, corporates are beginning to realize that the larger society's perception of corporates has a bearing on their capacity to function effectively and create shareholder value. Although spending on CSR continues to be a voluntary act in the rest of the world, it is mandated by law in India. Companies are required to spend a minimum percentage of their profits on a specified category of activities to fulfill their obligation to society. This legal requirement came into effect in 2014.The case documents the response of the Torrent Group to the new requirement. The Group was already voluntarily engaged in philanthropy. With the mandated spending on CSR, the Group's spending on social intervention would rise substantially. The case describes how the Group formulated and started executing its CSR strategy. The process required interpretation of the legal requirement; identification of the areas of intervention, with justifications for the choices made; and a strategy for executing the CSR program.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Social responsibility of business -- India -- Case studies